PENGARUH PEMBERIAN RANSUM PABRIK DENGAN PENAMBAHAN DAUN PEPAYA DAN DEDAK PADI TERHADAP PERSENTASE KARKAS AYAM KAMPUNG SUPER - Maulana, M. Ikhtisyamul; Hamdani, Asrul; Budiman, Cecep; Arullah, Arullah; Sudirman, Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Super native chickens are a cross between native chickens and laying hens. Super native chickens require nutritious feed to achieve optimal production results. This study aims to determine the effect of providing factory rations with the addition of papaya leaves and rice bran on the carcass percentage of super native chickens. The study was conducted from January 2026 to March 2026 using a completely randomized design with 5 treatments and 4 replications. Data analysis was carried out through analysis of live weight, carcass weight, and carcass percentage using analysis of variance in a completely randomized design (CRD). The results showed that all research variables, such as live weight, carcass weight, and carcass percentage, had the highest average values ​​in the P0 treatment with the 50% Factory Ration + (100% Papaya Leaves + 0% Rice Bran), with an average live weight ranging from 927-1028 grams per head, a carcass weight of 607-676 grams per head, and an average carcass percentage ranging from 64.38-65.87%.